COMMUNICATION MANAGEMENT (PR) IN DEVELOP EDUCATIONAL INSTITUTIONS AT NU WRINGIN VOCATIONAL SCHOOL - Wali, Mohammad (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2023)
School and community are an inseparable unit. Schools as local educational institutions and social organizations are responsible for determining the fate of future generations, and the community is not only a consumer, but also has a role and responsibility in the success or failure of education. The wider community, including parents of students, government agencies, business agencies/institutions, etc. The main purpose of socialization is for alumni and agencies to care, trust and use their services. As is happening today, many institutions, especially educational institutions, are facing a crisis of public confidence in carrying out their programs on a daily basis. Given this, the role of public relations in an internal organization of institutions or educational institutions is very important. Because public relations are actually practitioners who act as intermediaries between institutions and the community (or the community itself), PR is equally accountable to the institutions they represent and to the communities concerned. I'm in debt.